2021
DOI: 10.1242/dev.191197
|View full text |Cite
|
Sign up to set email alerts
|

An early global role for Axin is required for correct patterning of the anterior-posterior axis in the sea urchin embryo

Abstract: Activation of Wnt/β-catenin (cWnt) signaling at the future posterior end of early bilaterian embryos is a highly conserved mechanism for establishing the anterior-posterior (AP) axis. Moreover, inhibition of cWnt at the anterior end is required for development of anterior structures in many deuterostome taxa. This phenomenon, which occurs around the time of gastrulation, has been fairly well characterized but the significance of intracellular inhibition of cWnt signaling in cleavage-stage deuterostome embryos … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…To investigate the possibility that sp5 is a target of Wnt/β-catenin signaling, we first performed phylogenetic footprinting analysis and identified two predicted transcription factor binding sites (TFBSs) for TCF/LEF within a highly conserved and open chromatin region upstream of the 1 st exon of sp5 ( Figure S2 A) . Encouraged by these results we next prevented β-catenin nuclearization by injecting axin mRNA 12 , 40 and found that endomesoderm and equatorial ectoderm cells showed downregulation of sp5 transcripts at the mesenchyme blastula stage ( Figures 2 Ba, b and S6 B) while at the same time foxq2 was expressed broadly throughout embryos from the same injected mating pairs as observed in previous studies 12 , 19 ( Figure 2 Bd, e). LiCl treatment upregulates Wnt/β-catenin signaling in embryos, converting them into endoderm and mesoderm.…”
Section: Resultssupporting
confidence: 64%
“…To investigate the possibility that sp5 is a target of Wnt/β-catenin signaling, we first performed phylogenetic footprinting analysis and identified two predicted transcription factor binding sites (TFBSs) for TCF/LEF within a highly conserved and open chromatin region upstream of the 1 st exon of sp5 ( Figure S2 A) . Encouraged by these results we next prevented β-catenin nuclearization by injecting axin mRNA 12 , 40 and found that endomesoderm and equatorial ectoderm cells showed downregulation of sp5 transcripts at the mesenchyme blastula stage ( Figures 2 Ba, b and S6 B) while at the same time foxq2 was expressed broadly throughout embryos from the same injected mating pairs as observed in previous studies 12 , 19 ( Figure 2 Bd, e). LiCl treatment upregulates Wnt/β-catenin signaling in embryos, converting them into endoderm and mesoderm.…”
Section: Resultssupporting
confidence: 64%
“…In echinoderms, the early β-catenin-dependent specification of the endomesodermal domain is followed by the segregation of the endoderm from the mesoderm, and the subsequent Wnt-dependent PA patterning. In the endoderm, β-catenin signaling remains strong, while in the mesoderm β-catenin signaling becomes suppressed (Lhomond et al, 2012; Logan et al, 1999; McCauley et al, 2015; McClay et al, 2021; Range et al, 2013; Sun et al, 2021; Wikramanayake et al, 1998; Wikramanayake et al, 2004). A similar sequence of events – the early β-catenin-dependent definition of the future endodermal domain, the formation of the boundary between the β-catenin-sensitive future oral ectoderm and the β- catenin-insensitive future endoderm, and the subsequent Wnt-dependent OA patterning of the ectoderm also occurs in Nematostella , and these events seem to follow the same regulatory logic as described for the sea urchin.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbation experiments showed that augmentation of β-catenin throughout the embryo causes all cells to become endoderm, while inhibition of β-catenin accumulation results in a completely animalized embryo that expresses ectoderm markers only (Emily-Fenouil et al, 1998;Logan et al, 1999;Wikramanayake et al, 1998). Later studies with a GFP tagged form of β-catenin further showed that the β-catenin is actively destroyed in the animal hemisphere (Weitzel et al, 2004), while its initial accumulation, at least in the micromere nuclei, appears to be due, not to a Wnt signal, but to absence of Axin from these cells (Sun et al, 2021). Axin normally promotes destruction of β-catenin to prevent its accumulation (Zeng et al, 1997), so this early accumulation of β-catenin likely occurs in the absence of a Wnt signaling input.…”
Section: Conditionally Specified Endomesoderm In the Sea Urchinmentioning
confidence: 99%